Formulation and Characterization of Soy- free Meal Replacement Drink - Siti Nurul Natasya binti Mazlan; Malik, Nur Hafizah (Enhanced Knowledge in Sciences and Technology, 2023)
Meal replacement is typically formulated with plant based-protein, complex carbohydrates, healthy fats, and micronutrients to provide healthy calories in fewer amounts than one commonly consumed during a meal (breakfast, lunch, dinner). Increasing obesity in Malaysia makes people concerned about their health. Meal replacement should contain all essential nutrients such as protein, carbohydrates, fat, fibres, vitamins, and mineral. The study aims to investigate consumer acceptance of soy-free meal replacement drink through a market survey, formulate meal replacement drink using pea protein and characterize the physicochemical properties, nutritional content, and sensory and particle morphology. This study started with a market survey about the acceptance of soy-free meal replacement drinks. Next, the formulation of the meal replacement drink had been developed with three samples. The sensory analysis had been conducted by using a hedonic sensory test to see the acceptance from the consumers. Besides that, physicochemical like pH analysis, TSS, solubility, wettability, color, moisture content, and nutritional composition had been conducted. The particle morphology of three samples had been measured by Scanning Electron Microscope (SEM). The result from the Analysis of Variance (ANOVA) showed a significant difference between the three samples. For the sensory, pea protein was the most preferred by the panellists. For the nutrition content, energy was 360.333±1.528kcal/100g, carbohydrate was 56.733±0.321%w/w, the protein was 20.367±0.351%w/w, the total sugar was 37.433±0.153%w/w, total fat was 1.033±0.578w/w, Vitamin D was 1.633±0.058 mcg/100g, and Magnesium was 536.533±0.231mg/kg. For morphology, all samples have irregular shapes and sizes. In the future, other legumes can be studied to be added to the drink to make it high protein content.